Pengembangan Media Penjualan Pada Toko Store Anak Branded Dengan E-commerce - Atha Shalih Fatin; Safitri Juanita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The Covid-19 pandemic had an impact on "distro" business players so that turnover has fallen by up to 50%. One of them is a distribution called Toko Store Anak Branded which sells branded clothes in the Graha Raya area of ​​South Tangerang. Currently, the process of buying and selling transactions is carried out only in stores and WhatsApp social media, and has experienced a significant impact during the pandemic with a decline in sales transactions. So that research is needed to develop an E-Commerce-based sales media for children's fashion stores, named Toko Store Anak Branded. The method used is Business Model Canvas (BMC), with E-Commerce implementation using CMS Wordpress and Woocommerce Plugin and evaluating using blackbox. The conclusion of this study is that the development of sales media in Toko Store Anak Branded with E-Commerce is going well. Implementation of sales media at the Branded Children's Store Store has been implemented on the https://storeanakbranded.com/ site and can be accessed by the wider community. The implementation of a sales strategy using SEO techniques also went well, as evidenced in May 2022 appearing on the first page of Google on the keyword "base bomber storeanakbranded". The transaction documentation process is recorded properly and neatly, and makes it easier for store owners to find out store revenues quickly.